2011
DOI: 10.1002/pca.1378
|View full text |Cite
|
Sign up to set email alerts
|

Towards an Efficient Protocol for the Determination of Triterpenic Acids in Olive Fruit: A Comparative Study of Drying and Extraction Methods

Abstract: This study provides a rapid and low-cost extraction method, i.e. ultrasonic assisted extraction with an eco-friendly solvent such as ethanol, from frozen or lyophilised olive fruit for the accurate determination of the triterpenic acid content in olive fruit.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
27
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 34 publications
3
27
1
Order By: Relevance
“…Considering that the EtOH:MeOH (1:1) mixture extracted around 100% of MA and OA, then, we found that MeOH 100% only extracted 75% from the total of both triterpenic acids while MeOH 80% yielded only a 77% of MA and 26% of OA. Our results confirmed that the percentage of organic solvent is critical due to the high hydrophobicity of the analytes, and are in agreement with Goulas and Manganaris [30] which reported that, when using solid-liquid extraction, the EtOH:MeOH (1:1) mixture was the most efficient to recover triterpenic acids from olives.…”
Section: Optimization Of the Extraction Of Pentacyclic Triterpenessupporting
confidence: 95%
See 1 more Smart Citation
“…Considering that the EtOH:MeOH (1:1) mixture extracted around 100% of MA and OA, then, we found that MeOH 100% only extracted 75% from the total of both triterpenic acids while MeOH 80% yielded only a 77% of MA and 26% of OA. Our results confirmed that the percentage of organic solvent is critical due to the high hydrophobicity of the analytes, and are in agreement with Goulas and Manganaris [30] which reported that, when using solid-liquid extraction, the EtOH:MeOH (1:1) mixture was the most efficient to recover triterpenic acids from olives.…”
Section: Optimization Of the Extraction Of Pentacyclic Triterpenessupporting
confidence: 95%
“…Instead of drying the pulp at 105 • C to constant weight, a process reported to affect the estimated triterpenic acid content [30], the pulp was grinded in order to break down the fruit tissue and yield a fine and consistent suspension. This homogenization facilitated the second step, Table 3 Effect of the volume of the solvent and number of extraction cycles on the analysis of pentacyclic acids from Marfil Results of three independent samples analyzed in triplicate.…”
Section: Optimization Of the Extraction Of Pentacyclic Triterpenesmentioning
confidence: 99%
“…Previous studies have also demonstrated the superiority of FD as compared to common drying methods for diverse plant materials (Harbourne et al 2009;Rios & Gutiérrez-Rosales 2010;Goulas & Manganaris 2012). The benefits of FD can be attributed to the fact that this technique minimises the degradation of heat-sensitive spearmint compounds such as antioxidant phenols because the dehydration of the plant material is performed at low temperatures (Chou & Chua 2001).…”
Section: Resultsmentioning
confidence: 99%
“…The benefits of FD can be attributed to the fact that this technique minimises the degradation of heat-sensitive spearmint compounds such as antioxidant phenols because the dehydration of the plant material is performed at low temperatures (Chou & Chua 2001). In addition, the FD enhances the extractability of phenolic compounds from the dried spearmint since ice crystals formed within the sample matrix can rapture the cell structure, which allows the exit of cellular components and the access of solvent (Goulas & Manganaris 2012).…”
Section: Resultsmentioning
confidence: 99%
“…The significance of extraction in developing analytical methodologies for accurate estimation of bioactive compounds in functional foods has been highlighted by Goulas and George (2011).…”
Section: F Elkotb Etalmentioning
confidence: 99%